The genome sequences of the diplonemid protist Rhynchopus euleeides YPF1915 and its bacterial endosymbiont Candidatus Syngnamydia salmonis (Chlamydiota) [version 1; peer review: 3 approved] - Eerik Aunin; Victoria McKenna; Julius Lukeš; Drahomíra Faktorová; John M. Archibald; Daria Tashyreva; Aleš Horák; Elizabeth Sinclair; Graeme Oatley; Camilla Santos; Noah Gettle; Haoyu Niu; et al. (Wellcome Open Research)
We present a genome assembly of the diplonemid Rhynchopus euleeides (Euglenozoa; Diplonemea; Diplonemea; Diplonemidae). The genome sequence is 199.0 megabases long, with most of the assembly scaffolded into 88 chromosomal pseudomolecules. The multipartite mitochondrial genome and the 2.0 megabase genome of Ca. Syngnamydia salmonis, a bacterial endosymbiont of R. euleeides, were also sequenced and assembled.